2015
DOI: 10.1186/s12889-015-2388-8
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional serosurvey on hepatitis B vaccination uptake among adult patients from GP practices in a region of South-West Poland

Abstract: BackgroundHepatitis B is a significant health burden in Poland with nosocomial transmission being the main source of infection. Therefore, HBV vaccination is widely recommended for those not covered by the national immunisation program. Objective: To assess the coverage and influencing determinants of HBV vaccination among adult patients attending GP clinics as well as to establish serological status in terms of HBV infection.MethodsPatients who were seen consecutively in March 2013 at four randomly selected G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
1
8
0
1
Order By: Relevance
“…Our results also fit with the incidence rate of acute HBV infection in the Arkhangelsk Region, which has decreased more during last 20 years than in other regions [ 11 , 24 ]. The prevalence of anti-HBc among our participants was close to that reported in Poland, where 10.3% of adults were positive for this marker [ 25 ]. Data from Tajikistan showed that 30% of 15–24-year-olds are positive for anti-HBc, compared to 47% of adults aged 20–59 years in China, and 57.4% of adults aged 20–39 years in Nigeria [ 16 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results also fit with the incidence rate of acute HBV infection in the Arkhangelsk Region, which has decreased more during last 20 years than in other regions [ 11 , 24 ]. The prevalence of anti-HBc among our participants was close to that reported in Poland, where 10.3% of adults were positive for this marker [ 25 ]. Data from Tajikistan showed that 30% of 15–24-year-olds are positive for anti-HBc, compared to 47% of adults aged 20–59 years in China, and 57.4% of adults aged 20–39 years in Nigeria [ 16 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 83%
“…Data from Tajikistan showed that 30% of 15–24-year-olds are positive for anti-HBc, compared to 47% of adults aged 20–59 years in China, and 57.4% of adults aged 20–39 years in Nigeria [ 16 , 26 , 27 ]. Data from other parts of the world demonstrate that the higher the proportion of the vaccinated population, the lower the proportion of HBV-infected individuals: in Poland 55% of the adult population is vaccinated, and in China and Nigeria these values are 23.7% and 7.9%, respectively [ 16 , 25 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…We identified three sources for targeted vaccination programmes: the European Centre for Disease Prevention and Control (ECDC) [12], the Vaccine European New Integrated Collaboration Effort (VENICE) [13] and the European Liver Patients Association (ELPA) [14]. For 18 countries, we found additional sources on their vaccination programmes for indication groups MSM or people with frequently changing sexual partners [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Furthermore, contact persons from 34 European countries answered our short survey.…”
Section: Vaccination Programmesmentioning
confidence: 99%
“…Another study, conducted by us in 2013 among patients attending a primary care clinic, revealed that planned elective surgery was the main reason for their HBV immunization; similar rates were observed among adult patients from the Polish city of Katowice [10, 11]. …”
Section: Discussionmentioning
confidence: 74%